Buddhist values and moral attitudes of Ekayana junior high school students Dharma Budhi Bhakti - Anggiyanto Anggiyanto; Vike Aprilianin Marwintaria Saputri; Sutiyono Sutiyono (International Journal of Science and Applied Science: Conference Series, 2025)
The development of students' moral attitudes is an important aspect that needs serious attention in education, especially amid increasingly complex challenges. Teachers and parents are not only tasked with imparting academic knowledge, but also have a role as role models in shaping students' character and moral attitudes. This study aims to determine the influence of Buddhist values on the moral attitudes of students at Ekayana Dharma Budhi Bhakti Junior High School and to measure the extent to which this influence contributes to the formation of students' morals in the school environment. This study uses a quantitative approach with a survey method as a data collection tool. The research instrument, in the form of a questionnaire, was distributed to 41 respondents, namely junior high school students, using a Likert scale as a measuring tool to assess their level of understanding and application of Buddhist values and their moral attitudes in daily life. The collected data were then analyzed using simple linear regression techniques, with the help of the SPSS version 27 for Windows program to test the established hypotheses. The results showed that there was a positive and significant influence of Buddhist values on students' moral attitudes, with a contribution of 86.9%. This finding indicates that the higher the internalization of Buddhist values such as ethics (sīla), self-control (samādhi), and wisdom (paññā), the more positive the moral attitudes shown by students. This study is expected to be a reference for schools, especially religious-based schools, in developing a character education model that not only focuses on academic aspects but also instills moral and spiritual values comprehensively. That way, the learning process can shape students to have good character, self-control, and act wisely in accordance with religious values.